The Rural School Problem in 1999: A Review and Critique of the Literature - Patricia J. Kannapel; Alan J. DeYoung (Journal of Research in Rural Education, 1999)
This article reviews key literature on rural education published in the last 25 years. We provide an overview ofthe characteristics and conditions ofrural schools, followed by a discussion ofthe current"rural school problem" and how it developed. We then share various authors' notions ofwhat appropriate rural school improvement projects should (or do) look like. We conclude with a discussion ofthe key issues, and recommendationsfor future directions in the field of rural education.